Secularism, assimilation and the crisis of multiculturalism: French modernist legacies - Jansen, Yolande (IMISCOE research 2213-5421, 2013)
1. Introduction: the crisis of multiculturalism, new assimilationism and secularism -- 2. Assimilation in the French sociology of incorporation from a multicultural perspective -- 3. The liberal sociology of assimilation and citizenship and its transnationalist alternatives -- 4. Alfred Bloch's personal integration test at the threshold of his friend's home -- 5. Stuck in a revolving door -- 6. Elements of a critique of the laïcité-religion framework -- 7. Secularism, sociology and security -- 8. The highly precarious structure of assimilation: modernist philosophical schemes, memory and the Proustian narrative -- 9. Concluding remarks.